Coronary artery disease in post-COVID patients: a prospective study - Chhabra, Abhinav; Shisode, Vinod; Rajput, Richa (International Journal of Research in Medical Sciences, 2021)
Background: Corona virus disease 2019 or COVID-19 is defined as infectious illness caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). The cardiovascular manifestations of COVID-19 has been a topic of immense interest amongst epidemiologists, physicians and cardiologists alike. Cytokine storm seen in patients with COVID-19 is known to cause damage to multiple organs including cardiac myocytes. Coronary arteries are also affected by direct damage as well as cytokine mediated injury to coronary endothelial cells. Methods: This was a prospective study conducted in the department of cardiology of a tertiary care hospital. 40 patients recovered from COVID-19 and having symptoms related to coronary artery disease were included in this study on the basis of a predefined inclusion and exclusion criteria. The presenting complaints such as chest pain, breathlessness and fatigue were asked for and were documented. An informed written consent was obtained from all the participants. A standard Judkins technique was used to do coronary angiography. Severity of stenosis was assessed in all the cases. The statistical analysis was done using SSPS 21.0 software. P value less than 0.05 was taken as statistically significant. Results: Out of 40 post COVID-19 patients presenting with symptoms attributable to coronary artery disease there were 34 (85%) males and 6 (15%) females with a M:F ratio of 1:0.17. The mean age of male and female patients was found to be 51.33±6.47 years and 44.50±6.82 respectively. 12 (30%) patients had history of hypertension, 8 (20%) had history of diabetes mellitus. 3 (7.5%) patients had history of asthma. Chest pain (95%), breathlessness (67.5%), reduced exertional capacity (55%) and diaphoresis (40%) were common presenting complaints. Slow flow due to endothelial dysfunction was the most common single finding and was seen in 8 (20%) patients. In 7 (17.5%) 51-60% stenosis with thrombosis was found whereas in 6 (15%) patients 81-90% stenosis with thrombosis was seen. In 3 (15%) patients 70-80% stenosis with thrombosis was found and in remaining 3 (7.5%) total occlusion was seen. Conclusions: A high index of suspicion and timely intervention is necessary to diagnose and manage coronary artery disease in post covid patients.